2017
DOI: 10.1590/0103-8478cr20140452
|View full text |Cite
|
Sign up to set email alerts
|

Grafting technique and rootstock species for the propagation of Plinia cauliflora

Abstract: One of the biggest challenges for expansion of jabuticaba fruit tree cultivation is the high cost of seedlings due to to difficulties with vegetative propagation. Here, we aimed to evaluate graft survival in combinations of Plinia cauliflora and rootstocks of other species from the Myrtaceae family. The study was carried out at the Universidade Tecnológica Federal do Paraná - Campus Dois Vizinhos, Paraná State, Brazil. Eugenia uniflora L., E. involucrata DC, and P. cauliflora were used as rootstocks and were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 8 publications
0
5
0
1
Order By: Relevance
“…Graft take success in apple cultivars grafted on different rootstocks was evaluated and it was found that the cultivar Gala mast grafted on crab apple rootstock by means of bench grafting showed maximum graft take success as well as prominent growth ( Fazal et al, 2014 ). Whip and cleft grafting methods have been reported to be the most promising ones for the asexual propagation of Jabuticabeira Acu grafted on rootstocks belonging to other species of the same family ( Cassol et al, 2017 ). Depending upon the research purposes other grafting methods like in vitro grafting have been introduced.…”
Section: Grafting Techniques In Fruit Treesmentioning
confidence: 99%
“…Graft take success in apple cultivars grafted on different rootstocks was evaluated and it was found that the cultivar Gala mast grafted on crab apple rootstock by means of bench grafting showed maximum graft take success as well as prominent growth ( Fazal et al, 2014 ). Whip and cleft grafting methods have been reported to be the most promising ones for the asexual propagation of Jabuticabeira Acu grafted on rootstocks belonging to other species of the same family ( Cassol et al, 2017 ). Depending upon the research purposes other grafting methods like in vitro grafting have been introduced.…”
Section: Grafting Techniques In Fruit Treesmentioning
confidence: 99%
“…Os mais recentes estudos sobre pegamento pelo método da enxertia, seja por CF ou FL, foram encontrado valores de 20% para jabuticaba (Plinia cauliflora), 21% em camucamu (Myrciaria dubia) e 59% em goiabeira ( Psidium guajavaL.) (CASSOL et al, 2017;VANAJA et al, 2017;PINEDO-PANDURO et al, 2022). Espécies da família Myrtaceae comumente apresentam problemas na propagação vegetativa devido à presença de compostos fenólicos tóxicos que dificultam os processos de formação de calos e a cicatrização da união do enxerto e porta enxerto, podendo ocasionar a morte dos tecidos, o que resulta em insucesso da enxertia (LATTUADA et al, 2010).…”
Section: N C O N T R a S T T O T H E R E S U L T S O B T A I N E D W ...unclassified
“…The purpose of propagation through grafting is to maintain clone traits, obtain strong plants, improve unwanted plant species, accelerate tree growth and stem straightness, and accelerate fruiting plants [2,3]. Grafting has been used as a propagation method to increase vigour, uniformity, and robustness to the biotic and abiotic stresses of vegetatively regenerated plants [4,5].…”
Section: Introductionmentioning
confidence: 99%